ISSUES OF MENTAL EDUCATION IN THE DEVELOPMENT OF YOUTH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article describes some aspects of the development of mental education in the development of young people, the essence, tasks and attitudes of Eastern thinkers to the issues of knowledge and human mental thinking, mental education is the main criterion that determines the path of human life.